2012
DOI: 10.4103/0971-6580.97211
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C attenuates chronic chlorpyrifos-induced alteration of neurobehavioral parameters in Wistar rats

Abstract: Background:Oxidative stress is one of the molecular mechanisms in chlorpyrifos toxicity. The present study was designed to evaluate the attenuating effect of vitamin C on chlorpyrifos-induced alteration of neurobehavioral performance and the role of muscle acetylchloinesterase (AChE), glycogen and lipoperoxidation in the accomplishment of this task.Materials and Methods:Male rats were randomly assigned into 4 groups with the following regimens: soya oil (S/oil), vitamin C (VC), chlorpyrifos (CPF) and vitamin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The behavioural response of each rat to handling was assessed using excitability score test (Adeiza and Minka, 2010;Ambali and Ayo, 2012). The test exploits the reaction of the animal to handling and on this basis, the level of response can be graded or scored.…”
Section: Behavioural Assessmentsmentioning
confidence: 99%
“…The behavioural response of each rat to handling was assessed using excitability score test (Adeiza and Minka, 2010;Ambali and Ayo, 2012). The test exploits the reaction of the animal to handling and on this basis, the level of response can be graded or scored.…”
Section: Behavioural Assessmentsmentioning
confidence: 99%
“…The inhibition of BChE activity observed in the treated rats could result in impaired behavioral and muscle strength and analgesic effects. Ambali and Ayo [60] reported comparable results with chlorpyrifos, the metabolite of Judo 40. On day one posttreatment, the highest dose produced a 50% inhibition of BChE, indicating interference with cholinergic receptors as a result of the down-regulation of a muscarinic receptor concentration in the pons/medulla of rats [61].…”
Section: Discussionmentioning
confidence: 79%
“…The righting reflex response is another important behavioral endpoint widely used in toxicology to assess overt neurotoxic effects of OPs pesticides. For example, rodents exposed to CPF decrease their righting performance or lose the reflex altogether [89][90][91][92]. Previous studies in bats have also found the righting reflex response to be a sensitive indicator of OPs neurotoxicity, with righting latency being positively correlated with pesticide dose [12,76,93].…”
Section: Discussionmentioning
confidence: 97%